Technology, communication, disparities and government options in health and health care services - Kronenfeld, Jennie J. (Research in the sociology of health care ;, 2014)
This volume includes papers related to issues of technology, communication, health disparities and government options in health and health care services. It fills an existing gap by providing a clear sociological overview and focus on these topics. Technology is considered from the perspectives of providing healthcare equity, health disparities and the impact on doctor-patient relationships. The topic of communication is addressed in the format of public health messages and the use of internet chat rooms for discussions about health care services. Government roles and responsibilities are reflected upon in terms of health promotion, marketing and sales of health-related products and improving long-term care programs. Particular mention is made to learning lessons from the experiences and perspectives of other countries. Finally, health disparities are considered in socioeconomic terms, with particular reference to aging, depression, measures of health and healthcare in rural locations.